Perspective of Consumer Satisfaction at Ramen and Burger Restaurants in Terms of Product, Price and Location: Comparative Study of Direct Consumers and Consumers Grab Food - Atika Aini Nasution; Tri Auri Yanti; M. Asyari Syahab; Rianto Rianto (Pusat Riset dan Inovasi Nasional, 2024)
From the initial research that researchers did, the Ramen and Burger House was a place to eat that sold Japanese specialties and others. This Ramen and Burger House sets prices that are relatively cheap and can be reached by all levels of society. This is a very good strategy to survive in competition with similar companies. Besides setting a relatively cheap price, the Ramen and Burger Houses also always provide a variety of quality products for all consumers. Currently there are more than 77 types of products that are presented with good quality every day. Ramen and Burger houses offer a variety of products for consumers to choose, it will make the Ramen and Burger House more crowded by consumers. The purpose of this study was to determine whether there were differences in the effect of product, price and location on the satisfaction of direct consumers and consumers of Grab Food at Ramen and Burger Houses. The number of samples in this study was 100 people. The analysis technique used is multiple linear regression. The results showed that simultaneously product, price and location variables had a significant effect on consumer satisfaction both directly and through Grab Food at Ramen and Burger Restaurants. Product variables, price variables and location variables contribute to direct consumer satisfaction variables of 28.3% and the remaining 71.7% are determined by other variables outside the contribution of this study. For ordering through Grab Food, the product, price and location variables contribute to the consumer satisfaction variable of 22.6% and the remaining 77.4% is determined by other variables outside the contribution of this research.